Estimation of gingival crevicular fluid matrix metalloproteinase-3 levels in chronic periodontitis before and after scaling and root planing: A clinicobiochemical study - G Parab Prachi; Anunay Bhaskarrao Pangarikar; M V Devarathnamma; Shivanand Asapalli; Nagappa Guttiganur; Archana Devanoorkar (Wolters Kluwer Medknow Publications, 2022)
Context: Matrix metalloproteinases (MMPs) have widely been demonstrated in inflamed periodontal tissues and oral fluids. MMP3 is one of the MMPs which is effective in the degradation of numerous extracellular matrix substrates. It also participates in the proteolytic activation cascades of latent pro-MMP1, -8, and -9 which mediate collagenosis. Aims: This study aimed to estimate the gingival crevicular fluid (GCF) MMP3 levels in chronic periodontitis before and after scaling and root planing (SRP). Settings and Design: A total of 60 subjects aged 25-55 years are randomly selected from the outpatient department of periodontology of our institute and categorized into two groups of 30 each; Group I - periodontally healthy and Group II - generalized chronic periodontitis. Subjects and Methods: Clinical parameters such as plaque index, gingival index, probing depth, and clinical attachment loss were recorded in both groups. GCF was collected only once in Group I but twice in Group II. After the baseline records, Group II received SRP treatment followed by re-recording of clinical parameters and GCF sample collection 6 weeks posttreatment. GCF samples were analyzed for MMP3 molecule by enzyme-linked immunosorbent assay. Statistical Analysis Used: Data were analyzed by Student's t-test and Pearson's correlation coefficient. Results: All the clinical parameters showed improvements after the treatment procedure (P < 0.05). Baseline GCF MMP3 values in the test group were significantly higher than in controls (P < 0.05), and all the parameters decreased significantly after treatment (P < 0.05). Furthermore, the correlation between individual clinical parameters and biochemical parameter was positive but statistically insignificant (P > 0.01). Conclusions: Within the confines of this study, GCF MMP3 was increased in Group II subjects, suggesting its role in chronic periodontitis and the possibility of it being used as an early diagnostic biomarker.